Recent Trends in Thermal Engineering Select Proceedings of ICCEMME 2021 - Das, L. M.; Sharma, Abhishek; Hagos, Fitwi Yohaness; Tiwari, Sumit; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents select proceedings of the 3rd International Conference on Computational and Experimental Methods in Mechanical Engineering (ICCEMME 2021). It gives an overview of recent developments in the field of fluid dynamics and thermal engineering. Topics covered include case studies in thermal engineering, combustion engines, computational fluid dynamics (cfd), cooling systems, energy conservation, energy conversion, renewable energy, bio fuels, gas turbines, heat exchangers and heat transfer systems, heat pipes and pumps, heat transfer augmentation, refrigeration and HVAC systems, fluids engineering, energy and process, and thermal power plants. The book will be useful for researchers and professionals working in the area of thermal engineering and allied fields.
Transport Phenomena in a PWR Sub channel Replete with Al2O3-TiO2/Water Hybrid Nano fluid: A CFD Approach -- Performance Analysis and Optimization of Ammonia-CO2 and Ammonia-propylene refrigerant pairs for Cascade Refrigeration -- A comprehensive review of performance, combustion, and emission Characteristics of biodiesel fuelled diesel engines -- Analysis of Different Techniques of Superconductivity -- Prediction of the dynamic viscosity of MXene/palm oil nanofluid using support vector regression -- Experimental and Computational investigation of Coefficient of discharge of Venturimeter -- A comprehensive review of performance, combustion, and emissionCharacteristics of biodiesel blend with nanoparticles in diesel engines.
Keywords: Fluid mechanics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Production engineering; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer; Thermal Process Engineering; Fluid dynamics -- Congresses; Heat engineering -- Congresses